2010
DOI: 10.1039/c000009d
|View full text |Cite
|
Sign up to set email alerts
|

Physisorption of aromatic organic contaminants at the surface of hydrophobic/hydrophilic silica geosorbents: a B3LYP-D modeling study

Abstract: The adsorption of benzene and benzene-1,4-diol on two all-silica surface models derived from the framework of sanidine mineral with either hydrophobic or hydrophilic properties has been studied by means of periodic calculations based on local Gaussian basis function and the B3LYP-D functional, which includes dispersion contribution as an empirical correction to the pure B3LYP energy. The aromatic molecules have been docked on different adsorption sites of the two surfaces using the electrostatic potential of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 67 publications
(69 reference statements)
6
75
1
Order By: Relevance
“…Moreover, when adsorption is determined by dispersion interactions with siloxane groups and less by H-bonding, such a correction also becomes essential to determine the proper geometry and adsorption energy of the adsorbed adduct. An example of that is the work of Rimola et al 426 which studied the interaction of benzene, which can be considered as a partial analogue of the Phe molecule, with a hypothetical hydrophobic silica surface constituted by only Si-O-Si bonds; i.e., with no SiOH surface groups. Calculations were run adopting periodic boundary conditions (see Section 4.1) using B3LYP and B3LYP-D* methods, the latter inclusive of the dispersion contribution properly reparametrized 422 to account for the condensed matter nature of the system.…”
Section: Dispersion Correctionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, when adsorption is determined by dispersion interactions with siloxane groups and less by H-bonding, such a correction also becomes essential to determine the proper geometry and adsorption energy of the adsorbed adduct. An example of that is the work of Rimola et al 426 which studied the interaction of benzene, which can be considered as a partial analogue of the Phe molecule, with a hypothetical hydrophobic silica surface constituted by only Si-O-Si bonds; i.e., with no SiOH surface groups. Calculations were run adopting periodic boundary conditions (see Section 4.1) using B3LYP and B3LYP-D* methods, the latter inclusive of the dispersion contribution properly reparametrized 422 to account for the condensed matter nature of the system.…”
Section: Dispersion Correctionsmentioning
confidence: 99%
“…Along this line, it has been recently demonstrated that hydrophobic interactions indeed play an essential role which is clearly revealed when electrostatic and H-bonding interactions can be considered as constant. 426 In summary, it seems clear that the adsorption mechanism of AA on silica surfaces may be driven by three main kinds of contributions: i) electrostatic forces between AA ions and negatively charged SiO -surface groups, which become particularly favorable when the silica surfaces and AA exhibit a net charge of opposite sign achieved by modulating the pH; ii) H-bonding interactions between AA (either as neutral molecules or ions) and neutral SiOH groups; iii) hydrophobic interactions between the AA side chains and the siloxane Si-O-Si groups.…”
Section: General Trends Found In the Amino Acid Adsorption On Silica mentioning
confidence: 99%
See 3 more Smart Citations